1978
DOI: 10.1042/bj1690215
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the sequence of oxidative decarboxylation of the 2- and 4-propionate substituents of coproporphyrinogen III by coproporphyrinogen oxidase in rat liver

Abstract: Coproporphyrinogen oxidase (EC 1.3.3.3) catalyses the oxidative decarboxylation of the 2- and 4-propionate substituents of coproporphyrinogen III to form protoporphyrinogen IX. A 4-propionate-substituted porphyrinogen, harderoporphyrinogen, which is also a substrate for coproporphyrinogen oxidase, is formed during the reaction. Synthetic [(14)C]coproporphyrinogens III, specifically labelled in the carboxyl carbon atoms of either the 2- or 4-propionate substituents, were used to measure the rate of decarboxylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 24 publications
(31 reference statements)
1
27
0
Order By: Relevance
“…(A) Reaction catalyzed by CPO involves both oxidation and decarboxylation (5). CPO sequentially decarboxylates (26,30) the propionates attached to A and B rings without affecting those on C and D rings. A hydrogen atom from the ␤-position of the propionate side chain also is removed at each step (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…(A) Reaction catalyzed by CPO involves both oxidation and decarboxylation (5). CPO sequentially decarboxylates (26,30) the propionates attached to A and B rings without affecting those on C and D rings. A hydrogen atom from the ␤-position of the propionate side chain also is removed at each step (31,32).…”
Section: Resultsmentioning
confidence: 99%
“…If the reaction intermediate is able to reposition within the active-site cavity, this architecture would explain why the first decarboxylation, on the pyrrole A ring, is rate-limiting and rapidly followed by decarboxylation of the pyrrole B ring propionate (13,14). One potential advantage of the substrateinduced conformational change is that it might generate a specific pathway and binding site for the molecular oxygen cofactor, such as seen for cholesterol oxidase (42,43).…”
Section: Odcpo/hem13p Structurementioning
confidence: 99%
“…There are reports of requirements for copper (8) and manganese (9), although other studies found no metal ion or other cofactor dependence (except O 2 ) for odCPO activity (10 -12). Regardless of mechanistic details, the first decarboxylation has been shown to be the rate-limiting step for the overall reaction, and transient formation of the 3-carboxyl intermediate harderoporphyrinogen has been demonstrated (13,14).…”
mentioning
confidence: 99%
“…Harderoporphyrinogen is the natural intermediate between copro-and protoporphyrinogen. Isoharderoporphyrinogen (vinyl group on pyrrole B instead of pyrrole A) has not been isolated from tissues synthesizing protoporphyrin IX; however, isoharderoporphyrinogen is a known substrate of coproporphyrinogen oxidase (17). Me, methyl (-CH3); Pr, propionyl (-CH2-CH2-COOH); V, vinyl (-CH=CH2).…”
Section: Introductionmentioning
confidence: 99%